Papers of Paul Bourke - Bourke, Paul (Paul Francis), 1938-1999. (1954)
MS Acc00.260 comprises correspondence, conference papers, research files, files on university policy, especially relating to government policy such as the Dawkins Green Paper 1988, appointment diaries, lecture notes, articles and papers by other writers (32 boxes, 1 carton, 7 small cartons).
Manuscript reference no.: MS Acc00.260.
Historian, academic and university administrator. Paul Francis Bourke held continuing academic appointments at several Australian universities and visiting appointments in the United States and England, and a range of administrative appointments including acting deputy vice-chancellor of the Australian National University. In 1993, he was elected president of the Australian Academy of Social Sciences. Bourke's major field of research and publication was the social and political history of the United States, principally in the period 1840-1920, and, in 1995, he published Washington County: politics and community in antebellum America (with Donald DeBats). His other publications included A crisis for Australian science? (with Linda Butler, 1994), and Monitoring research in the periphery: Australia and the ISI indices (with Linda Butler and Beverley Biglia, 1996). Bourke had a long standing interest in the philosophy of history, and he worked extensively on issues in higher education and research policy.
Keywords: Bourke, Paul -- 1938-1999 -- Archives; Historians -- Australia -- Archives; College teachers -- Australia -- Archives; College administrators -- Australia -- Archives; History -- Philosophy; Higher education and state -- Australia; Research -- Australia -- Government policy; Historians; Academics; University administrators